Improving the Quality of Educators as a Factor in Renewing the Education System in Indonesia - Adha, Haidil; Novita, Ika; Chanifudin, Chanifudin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
In this day and age, the quality of educators is one of the factors in the education system, because in determining the quality of educators, the things that must be taken into account are personality and social competence. Quality educators must have a good personality, be authoritative, and be able to be a role model for students in terms of attitudes, behavior and positive values taught. This research uses a library research method. Literature review is a research activity that uses written sources as reference material to obtain information and data related to the topic being discussed. Sources of data and information are obtained from various literature such as books, articles, magazines, printed and online websites that are relevant to the discussion. The existence of good quality education can provide a reformed education system that has good quality for education in Indonesia in particular.